PERBANDINGAN PRESTASI BELAJAR ANTARA METODE CERAMAH DENGAN METODE EKSPERIMEN PADA POKOK BAHASAN REAKSI REDOKS DAN ELEKTROKIMIA DI SMA NEGERI 1, 2, DAN 3 BANDA ACEH INDONESIA - Muhammad Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
This research has aim to see the differences of learning achievement result by using lecture method and experimental method which applicated in redoks and electrochemistry discussions on students of SMA Negeri in Banda Aceh. In this research, the research used experimental method. As population is all of the students SMA Negeri Banda Aceh in class II Semester I 2008/2009 school year. Furthermore, as the sample of this research are SMA Negeri 1, SMA Negeri 2, and SMA Negeri 3. In addition, each of school taken two classes, that are the first class taught by using experimental method (experiment class), and the second class taught by using lecturer method (control class) and each class have 40 students. Thus, the total numbers of sampel in this research are 120 students in experiment class, and 120 students in control class. The instrument that used to know the students learning result is learning result test in redoks and electrochemistry discussions and it is multiple choice. Therefore, t-test of students learning result is used to examine the hypotheses both in experiment class and control class. The result of pretest that given are : the average of experiment class is 29,4 and for control class is 49,5. Moreover, the result of t-test both class are got t-count = 0,004 < t-table = 1,986 (α=0,005), in summary, there are no significant differences of result between experiment and control class. Furthemore, the result of posttest that given are : the average of the student experiment class is74,1, and for control class is 68,0. The t-test result of post-test for both classes are got t-count = 2,40 > t-table= 1,986 (α=0,05). Thus, there are significant differences of result between experiment and control class. It can be concluded that the student learning result of experiment class is higher than control class.